2019
DOI: 10.31464/jlere.528298
|View full text |Cite
|
Sign up to set email alerts
|

Türkçe Dersi 8. Sınıf Kitabındaki Metinlerin Okunabilirliği

Abstract: In this study, it was aimed to determine the word and sentence lengths of the texts of the 8th grade Turkish textbooks and to determine the readability levels of these texts and to examine the appropriateness of the texts to the class level. In this research carried out by the qualitative research methodology, the document review and its design were used. In the analysis of the data, descriptive analysis was used. As a result of this analysis, sentences and word lengths of the texts, frequency and percentage v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 3 publications
1
1
0
5
Order By: Relevance
“…Accordingly, it has been revealed that the 11th-grade textbook contains easier texts in narrative type and more difficult texts in informative type. It is seen that these results obtained support the results of the studies (Arı ve Okur, 2013;Baki, 2019;Baş ve İnan-Yıldız, 2015;Çiftçi, Çeçen ve Melanlıoğlu, 2007;Demir ve Çeçen, 2013;Özçetin ve Karakuş, 2020;Özdemir, 2016) conducted in the literature on the subject.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Accordingly, it has been revealed that the 11th-grade textbook contains easier texts in narrative type and more difficult texts in informative type. It is seen that these results obtained support the results of the studies (Arı ve Okur, 2013;Baki, 2019;Baş ve İnan-Yıldız, 2015;Çiftçi, Çeçen ve Melanlıoğlu, 2007;Demir ve Çeçen, 2013;Özçetin ve Karakuş, 2020;Özdemir, 2016) conducted in the literature on the subject.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…Buna göre bilgilendirici metinlerde okunabilirlik düzeyi çeşitliliğinin daha zengin olduğu şeklinde bir yorum yapılabilir. Farklı sınıf seviyelerindeki metinlerin incelendiği araştırmalarda da (Arı ve Okur, 2013;Baki, 2019;Demir ve Çeçen, 2013;Özçetin ve Karakuş, 2020;Özdemir, 2016) bu yargıyı destekleyen bulgular elde edilmiştir.…”
Section: Sonuç Tartışma Ve öNerilerunclassified
See 3 more Smart Citations